Une anticipation rationnelle de son orientation - Erwan Lehoux (Éducation et Socialisation)
Parcoursup is part of a global change in orientation. Students and their parents, who are considered to be actors of their own education. They are being encouraged to to be rational in their orientation choices, with reference notably to a pre-defined project. This article shows that hight school students are receptive to this expectation, while maintaining a more or less instrumental relationship with their schooling. Although almost all of them refer to a project, in practice it takes on different meanings depending on the student. This article examines the diversity of uses and expressions of the project approach among Year 10 students.